Annexin A1 levels affect microbiota in health and DSS-induced colitis/inflammatory bowel disease development - Filippi Xavier, Luana; Gacesa, Ranko; da Rocha, Gustavo Henrique Oliveira; Broering, Milena Fronza; Scharf, Pablo; Lima, Fabiana da Silva; Faber, Klaas Nico; Harmsen, Hermie; Hoffmann, Christian; Farsky, Sandra Helena Poliselli (Frontiers in Immunology, 2025)
BackgroundInflammatory Bowel Diseases (IBDs) are characterized by intestinal dysbiosis and immune dysregulation. Annexin A1 (AnxA1) promotes epithelial repair and inhibits immune responses during IBD. However, AnxA1’s impact on gut microbiota during IBD remains unclear. Here, we experimentally investigated the microbiota profile during colitis in wild-type (WT) and AnxA1-deficient mice (AnxA1-/-), and evaluated an observational cohort in IBD patients with high or low AnxA1 expression.MethodsColitis was induced in C57BL/6 WT and AnxA1-/- mice via oral administration of 2% DSS for six days. Fecal samples were collected at baseline, peak inflammation (day 6), and during the recovery phase (day 10) for 16S rRNA sequencing. Human microbiota data from the Lifelines Dutch Microbiome Project cohort, including IBD and healthy subjects, were analyzed for AnxA1 expression using R software.ResultsHealthy AnxA1-/- mice exhibited reduced microbial richness and a distinct gut microbiota composition, marked by increased Proteobacteria and Parasutterella, and reduced Deferribacterota, Campylobacterota, and Verrucomicrobiota. During DSS-induced colitis, AnxA1-/- mice showed greater weight loss and heightened inflammation, displaying earlier and more pronounced microbial shifts, including increased Proteobacteria, Cyanobacteria, Parabacteroides, Bacteroides, and Escherichia-Shigella. In contrast, WT mice exhibited delayed changes, with expansion of Alloprevotella, Akkermansia, and Faecalibaculum after day 6. In human IBD samples, Crohn’s disease (CD) patients with low AnxA1 expression and active inflammation presented an altered microbiota enriched in Lachnoclostridium and Parabacteroides, while ulcerative colitis (UC) patients showed phylum-level shifts modulated by AnxA1 levels. Notably, non-inflamed CD and UC patients with low AnxA1 differed significantly in microbiota composition. Moreover, inflamed CD patients with high AnxA1 expression showed microbial profiles resembling those of healthy controls, while low AnxA1 expression was associated with a more pronounced dysbiotic state.ConclusionAnxA1 is implicated in microbiota control under healthy and IBD conditions. Accordingly, the microbiota of healthy AnxA1-/- mice, colitic AnxA1-/- mice, and IBD patients with low AnxA1 expression exhibit dysbiosis compared to their respective controls. Together, these unprecedented findings reveal AnxA1 as a potential regulatory protein in the immune–microbiota axis involved in IBD pathogenesis.